Long-Term Outcomes of Cataract Surgery: Analysis of Visual Acuity and Intraocular Pressure in a Tertiary Care Center - Nursalim, Ade J.; Sumual, Vera; Chietra, Andrew; Emily, Ardelia; Rusli, Richardo (e-CliniC, 2024)
Abstract: Posterior capsule opacity (PCO) is a common complication following cataract surgery, caused by the proliferation of residual lens epithelial cells. This study aimed to evaluate the long-term effects of Nd:YAG laser capsulotomy on intraocular pressure (IOP) and visual acuity in PCO patients. This was a retrospective descriptive study. Samples were 24 patients diagnosed with PCO who underwent Nd:YAG laser capsulotomy at Prof. Dr. R. D. Kandou Hospital, Manado, from January 1, 2022, to January 1, 2024. The study recorded pre- and post-procedure IOP and best-corrected visual acuity (BCVA) data. Descriptive analysis, including paired t-tests, was used to assess changes in IOP and BCVA over an average follow-up period of 19.2 months. The results showed a statistically significant improvement in BCVA (p=0.000), with mean values improving from 0.72 to 0.27 LogMAR. A significant reduction in IOP was also observed (p=0.015), with long-term IOP remaining stable. A weak correlation was found between follow-up duration and IOP variation (p=0.02). In conclusion, Nd:YAG laser capsulotomy significantly improves visual acuity and stabilizes intraocular pressure in the long term for PCO patients, suggesting its effectiveness in managing post-cataract surgery complications. Keywords: posterior capsule opacity; Nd:YAG laser capsulotomy; intraocular pressure; visual acuity; cataract surgery